Adrenergic chromaffin cells are adrenergic even in the absence of epinephrine. Issue 3 (28th November 2019) - González‐Santana, Ayoze; Castañeyra, Leandro; Baz‐Dávila, Rebeca; Estévez‐Herrera, Judith; Domínguez, Natalia; Méndez‐López, Iago; Padín, J. Fernando; Castañeyra, Agustín; Machado, José‐David; Ebert, Steven N.; Borges, Ricardo
Abstract: Adrenal chromaffin cells release epinephrine (EPI) and norepinephrine (NE) into the bloodstream as part of the homeostatic response to situations like stress. Here we utilized EPI‐deficient mice generated by knocking out (KO) the phenylethanolamine N ‐methyltransferase (Pnmt) gene. These Pnmt‐KO mice were bred to homozygosis but displayed no major phenotype. The lack of EPI was partially compensated by an increase in NE, suggesting that EPI storage was optimized in adrenergic cells. Electron microscopy showed that despite the lack of EPI, chromaffin granules retain their shape and general appearance. This indicate that granules from adrenergic or noradrenergic cells preserve their characteristics even though they contain only NE. Acute insulin injection largely reduced the EPI content in wild‐type animals, with a minimal reduction in NE, whereas there was only a partial reduction in NE content in Pnmt‐KO mice. The analysis of exocytosis by amperometry revealed a reduction in the quantum size (−30%) and I max (−21%) of granules in KO cells relative to the wild‐type granules, indicating a lower affinity of NE for the granule matrix of adrenergic cells. As amperometry cannot distinguish between adrenergic or noradrenergic cells, it would suggest even a larger reduction in the affinity for the matrix. Therefore, our results demonstrate that adrenergic cells retain their structural characteristics despite the almost complete absence of EPI. Furthermore, the chromaffin granule matrix from adrenergic cells is optimized to accumulate EPI, with NE being a poor substitute. Open Science: This manuscript was awarded with the Open Materials Badge For more information see: https://cos.io/our-services/open-science-badges/ Abstract : The absence of functional phenylethanolamine‐ N ‐methyltransferase (Pnmt) results in a mouse without epinephrine (EPI). In the adrenal gland, this is only partially compensated by an increase in the adrenal content of norepinephrine (NE). This can be explained because secretory vesicles of adrenergic cells are optimized for storage and release EPI resulting in lower accumulation of the only available catecholamine, NE. The quantal exocytosis characteristics and the functional responses to stimuli suggest that adrenergic cells are still of adrenergic linage in spite of the lack of EPI.